Elucidating the Structural Organization of a Novel Low-Density Lipoprotein Nanoparticle Reconstituted with Docosahexaenoic Acid - Mulik, Rohit S. (Chem Phys Lipids, 2017)
Low-density lipoprotein nanoparticles reconstituted with unesterified docosahexaenoic acid (LDL-DHA) is promising nanomedicine with enhanced physicochemical stability and selective anticancer cytotoxic activity. The unique functionality of LDL-DHA ultimately relates to the structure of this nanoparticle. To date, however, little is known about the structural organization of this nanoparticle. In this study chemical, spectroscopic and electron microscopy analyses were undertaken to elucidate the structural and molecular organization of LDL-DHA nanoparticles. Unesterified DHA preferentially incorporates into the outer surface layer of LDL, where in this orientation the anionic carboxyl end of DHA is exposed to the LDL surface and imparts an electronegative charge to the nanoparticles surface. This negative surface charge promotes the monodisperse and homogeneous distribution of LDL-DHA nanoparticles in solution. Further structural analyses with cryo-electron microscopy revealed that the LDL-DHA nanostructure consist of a phospholipid bilayer surrounding an aqueous core, which is distinctly different from the phospholipid monolayer/apolar core organization of plasma LDL. Lastly, apolipoprotein B-100 remains strongly associated with this complex and maintains a discrete size and shape of the LDL-DHA nanoparticles similar to plasma LDL. This preliminary structural assessment of LDL-DHA now affords the opportunity to understand the important structure-function relationships of this novel nanoparticle.